Visual application of the American Board of Orthodontics grading system - Scott Steven A.; Freer Terry J. (Sciendo, 2005)
Background: Assessment of treatment outcomes has traditionally been accomplished using the subjective opinion of experienced clinicians. Reduced subjectivity in the assessment of orthodontic treatment can be achieved with the use of an occlusal index. To implement an index for quality assurance purposes is time-consuming and subject to the inherent error of the index. Quality assessment of orthodontic treatment on a routine basis has been difficult to implement in private practice.